KESIAPAN MASYARAKAT DALAM IMPLEMENTASI ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID - 19 - Windu Santoso; Sri Sudarsih (Universitas Harapan Bangsa Purwokerto, 2021)
At this time, Indonesia is preparing to enter a new normal life phase in the face of the Corona Virus pandemic. Several forms of changes or new transformations which later gave birth to the term